2004
DOI: 10.1038/sj.bjc.6602045
|View full text |Cite
|
Sign up to set email alerts
|

CIITA methylation and decreased levels of HLA-DR in tumour progression

Abstract: We read with interest the article of Morimoto et al (2004) that investigated the relation of epigenetic inactivation of CIITA with levels of HLA-DR, one of the MHC class II genes, in haematopoietic tumour cells.Recent DNA microarray studies have showed that decreased levels of MHC class II molecules are associated with high metastatic potential and/or poor prognosis, not only in haematopoietic tumour (Rimsza et al, 2004) but also in several adenocarcinomas (Ramaswamy et al, 2003) and hepatocellular carcinoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…(11). We found that the levels of CIITA, a transactivator of MHC class II genes, were markedly lower in HCC than in non-cancerous liver (33). This downregulation may be due to the epigenetic inactivation of CIITA.…”
mentioning
confidence: 76%
“…(11). We found that the levels of CIITA, a transactivator of MHC class II genes, were markedly lower in HCC than in non-cancerous liver (33). This downregulation may be due to the epigenetic inactivation of CIITA.…”
mentioning
confidence: 76%
“…We hypothesize that changes in expression of HLA II genes in HCC patients is related to CIITA expression levels. In gastrointestinal cancer cells and other types of tumors, the relationship between CIITA and HLA II gene expression has been associated with patient prognosis (21)(22)(23)(24)(25)(26)(27). These studies found that loss of CIITA expression contributed to the down-regulation of HLA II genes in tumors and lead to the immune escape of tumor cells.…”
mentioning
confidence: 84%
“…Based on these data, an increased knowledge concerning the underlying molecular processes controlling the expression of HLA class II APM components and their prognostic significance in MM is required. These might range from mutations in HLA class II regulatory genes [45] to transcriptional, posttranscriptional and epigenetic control [28,[46][47][48][49][50][51]. Furthermore, the immune-cell repertoire might influence the HLA class II expression, since HLA-class-II-pathway component expression has been shown to be associated with B and T cell infiltration [52].…”
Section: Introductionmentioning
confidence: 99%